Foreign exchange operation of a commercial bank of Bangladesh: a case of the Premier Bank Ltd, Kawran Bazar Branch - Arif, Md. Salehin (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2013.